Establishing a knowledge-based organisation: Lesson learnt and KM challenges in Malaysian organisation - Norzanah Mat Nor; Siti Murni Mat Khairi; Herwina Rosnan; Roozita Maskun; Elaina Rose Johar (Innovation & Management Review, 2020)
Purpose - Studies on knowledge management (KM) and its effect on organisational innovation and firm performance have been carried out and subsequently proven. However, the consequence is that KM programmes did not achieve the expected results that they were designed for. Considering the issue mentioned above, a KM shortfall and its underlying challenges seem to exist. The purpose of this study is to assess the current practices of KM, lesson learnt and KM challenges in Malaysian organisations from various types of industries. Design/methodology/approach The study was conducted with information gathered through a focus group of managers with different hierarchical levels, different types of companies, from multinational corporations to state organisations. This inductive approach was adopted to gain a grounded, rich, local and lived understanding of the process based on the case studies of eight Malaysian organisations that represent the major industries in the Malaysian economic sectors. Additionally, the information gathered was further supported with secondary data that consisted of a case study report of the eight organisations on their KM programmes' implementation. Findings The overall results showed that the practice of KM in Malaysian organisations typically displays the following two challenges: (1) process and infrastructure issues and (2) cultural issues. Organisational culture remains the main obstacles faced by most of the organisations in adopting KM. As a lesson learnt, managers should also focus on the after-effect of KM programmes on soft human issues such as employees' satisfaction and well-being. Research limitations/implications The authors believe that further research is required considering KM challenges and employee satisfaction or well-being to improve KM performance among different groups of employees through such methods as research survey. Practical implications The findings can act as a guideline for any organisations to address when adopting KM. Identification of the KM challenges provides the basis for organisations to attach considerable importance to employees' satisfaction and well-being to enhance the chances of successful KM programmes. Managers should take a proactive approach in creating an appropriate atmosphere to cultivate KM culture among employees. Originality/value This study offers not only challenges in implementing and sustaining an effective KM system within organisations but also promotes moving the KM literature to the next stage where there is a lack of concern on KM implementation effect on 'soft' human issues from the perspectives of employees. This is due to organisations tend to eradicate people's performance in terms of employee well-being and satisfaction and to the author's knowledge, this has been largely unexplored in previous research.
Keywords: 650; Employee satisfaction; KM challenges; Knowledge management; Well-being